1985
DOI: 10.3109/00365518509160995
|View full text |Cite
|
Sign up to set email alerts
|

Carnitine and left ventricular function in haemodialysis patients

Abstract: Left ventricular function was non-invasively studied in 28 randomly selected haemodialysis patients before and after administration of L-carnitine, 2 g i.v. three times per week or saline in a double blind designed study over a six-week period. Cardiac function variables showed no relationship to muscle (vastus lateralis) and plasma carnitine concentrations. No apparent deficiency in muscle carnitine was found, whereas total plasma carnitine was lower in female patients than in female controls, p less than 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
1

Year Published

1987
1987
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 18 publications
0
34
1
Order By: Relevance
“…Only 1 randomized double-blind controlled study about the relationship of L -carnitine and cardiac function has been reported so far [18]. Fagher et al [18] reported in 1985 that carnitine depletion is not responsible for cardiac dysfunction in patients on hemodialysis, but their patients had normal levels of skeletal and blood carnitine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 1 randomized double-blind controlled study about the relationship of L -carnitine and cardiac function has been reported so far [18]. Fagher et al [18] reported in 1985 that carnitine depletion is not responsible for cardiac dysfunction in patients on hemodialysis, but their patients had normal levels of skeletal and blood carnitine.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors noted an improvement [13,14,15,16,17], while others found no change [18,19,20]. Firstly, study limitations such as heterogeneity of the study group, non-randomized, non-double-blind studies, and investigators' potential bias must be taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17]23,24 Our study was conducted in a larger study cohort and the result provide more robust support for LC supplementation in patients with CHF. However, although significant, the effect of LC over placebo was not impressive.…”
Section: Discussionmentioning
confidence: 99%
“…11 There were also reports of improvement of cardiac dysfunction by L-carnitine supplementation, especially in patients with declined cardiac systolic function or with symptoms of heart failure; [12][13][14][15] however, when patients with normal myocardial function were studied, no benefit of carnitine was seen. 13,16 Left ventricular hypertrophy (LVH) is common and is an independent predictor of cardiac death in patients undergoing dialysis. 17 In these conditions, falls in the contraction index value are not seen or are mild, but there is expansion of the ventricular cavity and increased myocardial thickness and heart weight.…”
mentioning
confidence: 99%